Coxsackie Viruses and Diabetes Mellitus. Issue 5887 (3rd November 1973) - Gamble, D. R.; Taylor, K. W.; Cumming, H.
Abstract : Serum specimens from 162 patients with insulin-dependent diabetes of recent onset and 319 controls were tested for neutralizing antibodies to Coxsackie viruses types B1 to B5. Antibody to type B4 virus was more often found in diabetics than in controls, particularly in the 10-19 year age group. Though controls were not matched for geographical area it was thought that this was unlikely to explain the difference found. The month of onset of diabetes in the patients studied showed a pronounced seasonal incidence, which resembled that found in earlier studies.